(untitled) (Revista de Biología Marina y Oceanografía, 2024)
The morphology of the egg capsule and embryonic stages of Sympterygia brevicaudata are described. A total of 144 egg capsules were collected stranded on the beach and by scuba diving at a depth between 3 and 10 m, from Arica and Taltal, northern Chile, with a frequency of two days per month from March 2011 to March 2012 and from April 2012 to March 2013. The morphology and structures with which the female fixes the egg capsule to stable substrates are described. The observations on the late embryonic development were made using 72 embryos extracted from the 144 ovigerous capsules, which were kept in captivity. A total of seven embryonic stages were determined and described. In the initial stages (I to III) an embryo with an elongated structure was observed, with long and developed gill filaments, a translucent body and a pale pink color due to high blood supply and a large yolk sac. In later stages (IV to VII) the change in the morphology of the body disc was described due to the development of the pectoral and pelvic fins, appearance of ocular and body pigmentation, dorsal fins, dermal denticles and dorsal spines. The decrease and disappearance of the gill filaments and the yolk sac was documented. In conclusion, the detailed study of the egg capsule morphology and embryonic stages of S. brevicaudata provides a comprehensive insight into the early development of this species in coastal waters off northern Chile. Observations on egg capsule attachment and morphological changes during embryonic development highlight the adaptation and evolutionary process of this species in its natural habitat. This work contributes significantly to the understanding of reproductive biology and early development in rays of the genus Sympterygia, underlining the importance of conserving their ecosystem for preservation, especially in vulnerable species such as S. brevicaudata.